2004
DOI: 10.1016/s0006-3495(04)74341-6
|View full text |Cite
|
Sign up to set email alerts
|

Short Class I Major Histocompatibility Complex Cytoplasmic Tails Differing in Charge Detect Arbiters of Lateral Diffusion in the Plasma Membrane

Abstract: Directed and Brownian movement of class I major histocompatibility complex (MHC) molecules on cell membranes is implicated in antigen presentation. Previous studies indicated that the class I MHC cytoplasmic tail imposes constraints on the molecule's diffusion. Here we used single particle tracking to study the mobility of the wild-type mouse H-2L(d) class I MHC molecule and of seven cytoplasmic tail variants. Six of the variants have cytoplasmic tails of four or seven residues (differing in net charge), and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…More recently, it was shown that such nanoclustering strongly depends on the actin cytoskeleton, which acts as a barrier to spatially concentrate MHCI molecules (24). Consistent with these observations, deletion of the cytoplasmic tail increased the lateral mobility of MHCI (43). Clustering of MHCII complexes on the plasma membrane of APCs has also been reported (44)(45)(46).…”
Section: Discussionmentioning
confidence: 53%
“…More recently, it was shown that such nanoclustering strongly depends on the actin cytoskeleton, which acts as a barrier to spatially concentrate MHCI molecules (24). Consistent with these observations, deletion of the cytoplasmic tail increased the lateral mobility of MHCI (43). Clustering of MHCII complexes on the plasma membrane of APCs has also been reported (44)(45)(46).…”
Section: Discussionmentioning
confidence: 53%
“…Although very small, the three-amino-acid cytoplasmic tail of DR␤ acquires functional properties, in contrast to the fully truncated version with only the tyrosine residue. The lateral diffusion properties of the two molecules in the membrane could be drastically different and might influence the behaviour of Ii (Capps et al, 2004). However, before one can understand the role of the DR␤ chain, the means and chaperones involved in Iip35 retention will need to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although some systems show little change upon cytoplasmic tail deletion, 28 others show dramatic changes in receptor lateral mobility depending on the specific sequence 29 and length of the cytoplasmic domain. 28,30 This general mechanism influences the mobility of a large variety of immune cell receptors required for T cell activation. [31][32][33] Although cytoplasmic domain binding sites are clearly important for receptor interactions with cytoskeleton-associated proteins, it should be noted that these sites are often not static entities.…”
Section: Binding To Cytoskeleton or Associated Proteinsmentioning
confidence: 99%
“…52 An important component of the TCR counter-receptor, the MHC protein, also experiences lateral reorganization in the membrane. Both FPR 26,28,53 and SPT 30,54,55 studies have shown that the MHC protein is a highly mobile cell surface receptor, and its mobility is in part determined by its cytoplasmic tail. FRET [56][57][58] and single-molecule fluorescence imaging 59 studies have shown that MHC proteins also reorganize into oligomeric clusters.…”
mentioning
confidence: 99%